Effective delivery of osteopontin small interference RNA using exosomes suppresses liver fibrosis via TGF-β1 signaling - Min Tang; Cheng Guo; Mengxue Sun; Hao Zhou; Xin Peng; Jianli Dai; Qin Ding; Ying Wang; Changqing Yang (Frontiers in Pharmacology, 2022)
Objective and aims: Osteopontin (OPN), an oxidant stress sensitive cytokine, plays a central role in liver fibrosis. While OPN expression can be reduced by small interfering RNA (siRNA), the challenge to deliver siRNA safely and effectively into liver remains unresolved. Exosomes are promising natural nanocarriers for drug delivery that are able to enter cells with different biological barriers efficiently. In this study, we used exosomes as a delivery vehicle to target OPN in liver fibrosis.Methods: Exosomes selectively home to fibrotic liver according to small animal imaging system. Electroporation technique was used to engineer exosomes to carry siRNA targeting OPN (ExosiRNA−OPN). Primary hepatic stellate cells (HSCs) were isolated and treated with ExosiRNA−OPN to assess the effect on activated HSCs (aHSCs). Immunofluorescence for α−SMA, an aHSCs marker, and sirius red staining were performed to assess ECM deposition. Finally, plasma OPN from patients with liver fibrosis was identified by ELISA assay.Results: Exosome-mediated siRNA delivery systems show high uptake and low toxicity. Besides, ExosiRNA−OPN suppressed HSCs activation and ECM deposition and more efficiently improved liver function when compared to naked siRNA-OPN. Moreover, ExosiRNA−OPN was assumed inhibiting TGF-β1 signaling activation, along with other fibrotic-related genes based on a GEO datasheet of liver fibrosis samples for correlation analyzes. ExosiRNA−OPN inhibited TGF-β1 signaling by decreasing high-mobility group box-1 (HMGB1). Plasma proteins from chronic HBV-induced fibrosis patients were identified that patients with high OPN expression correlates with more advanced fibrosis progression.Discussion: This study shows that exosome-mediated siRNA-OPN delivery may be an effective option for the treatment of liver fibrosis.